Kehidupan Sosial Masyaraka Pada Tokoh Utama Dalam Novel Summer In Seoul Karya Ilana Tan - Rahmah, Alfiyah (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2021)
In a literary work, it can be interpreted as an expression of every human being which can be in the form of writing or verbally based on experiences, opinions, thoughts, to feelings and imaginative forms. This understanding is reinforced by Sumardjo and Saini (1997: 3) who have the opinion that literature is an expression of every human person in the form of an idea, experience, thought, spirit, belief, which in it has concrete properties that can evoke charm through language tools. In this case there is a novel which is one of the literary works that continues to experience the development of the times. Novels in literary works have an understanding as a form of literature that is very popular in the world even in all circles from young to old. While the novel that I am currently researching is a novel with a romantic genre, the novel is Summer in Seoul Novel. An inspiring novel, is the author's first novel to publish a Four Seasons Tetraogy novel. Summer in Seoul novel has a romance genre, the genre in the novel is usually favored by teenagers and this novel can be used as entertainment and creativity in the reader's imagination. The novel tells the story of a famous young Seoul singer named Jung Tae Woo who reappears after four years of avoiding the entertainment world. And a person named Sandy alias Han Soon Hee, a mulatto Indonesian-Korean girl who is currently studying in college and working as a designer at a well-known boutique in Seoul, South Korea. And the novel Summer in Seoul provides an overview of life's insights about the world of Entertainment, especially about a struggle in life to achieve dreams and strong will.